Acute total hip arthroplasty in acetabular fractures using modern porous metal cup - Malhotra, Rajesh (J Orthop Surg (Hong Kong), 2019)
PURPOSE: The aim of this study was to report the clinical and radiological outcome of using the modern porous metal cup in patients undergoing acute total hip arthroplasty (THA) for selected subset of acetabular fractures. PATIENT AND METHODS: Eighteen patients with acetabular fracture underwent acute THA with modern porous metal cup from a single manufacturer. Fifteen males and three females with a mean age of 46.4 years (range 21–57 years) were ambispectively followed up for a minimum period of 48 months. All patients were evaluated clinically with Harris Hip Scores (HHS) and radiographically with serial X-rays. RESULTS: No patient was lost to follow-up. The HHS was excellent in nine patients, good in six patients, fair in two patients, and poor in one patient. All the fractures were united and the cups were well integrated. There was no lucent line seen in any acetabular zones on the X-rays. One patient had infection, which resolved with debridement. There was one dislocation following fall, which was reduced by closed means and remained stable. One of the two patients with heterotopic ossification had restricted movement of hip but not restricting the activities of daily living. No failures of acetabular component were seen in the study. CONCLUSION: The current study showed that the modern porous metal cup provides sufficient primary stability and appear suitable for primary THA in acute acetabular fractures at mid-term follow-up: (i) In selected fractures, acute THA can be extended to young adult patients as well. (ii) Modern porous metal cup may provide sufficient stability with or without additional fixation required.